The Interpretation of the Flexibilities in the TRIPS Agreement in Light of the Right to Health - Garagancea, Lorelei (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional, 2025)
This article explores the interplay between the flexibilities embedded in the Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS) and the international human right to health, particularly in the context of access to affordable medicines. It critically examines how TRIPS provisions —especially Articles 7 and 8— can be interpreted in light of evolving human rights obligations under instruments such as the International Covenant on Economic, Social and Cultural Rights and the WHO Constitution. The analysis draws on the Doha Declaration and relevant jurisprudence to argue for a dynamic, evolutive interpretation of TRIPS flexibilities, including compulsory licensing, government use, and exhaustion regimes, emphasizing their potential to reconcile intellectual property protection with public health objectives. Furthermore, the article assesses the role of both state and corporate actors in realizing the right to health, considering recent legal developments such as the EU Corporate Sustainability Due Diligence Directive. It contends that fair pricing strategies and enhanced global cooperation are critical to ensuring equitable access to medicines, especially in light of global health emergencies and rising drug costs. Ultimately, the study advocates for a tailored, context-sensitive application of TRIPS flexibilities, aligned with both trade law and human rights law, to support sustainable and inclusive global health governance.